A note on the mean residual life of a coherent system with a cold standby component. Issue 20 (18th October 2017) - Mirjalili, Ahmad; Sadegh, Mohammad Khanjari; Rezaei, Majid
ABSTRACT: In this paper, we investigate the effect of a cold standby component on the mean residual life (MRL) of a system. When the system fails, a cold standby component is immediately put in operation. We particularly focus on the coherent systems in which, after putting the standby component into operation, the failure of the system is due to the next component failure. For these systems, we define MRL functions and obtain their explicit expressions. Also some stochastic ordering results are provided. Such systems include k -out-of- n systems. Hence, our results extend some results in literature.